2018
DOI: 10.1002/nau.23590
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an urethro‐vesical crosstalk mediated by serotonin

Abstract: Serotonin, produced and released by urethral cells activates an urethro-vesical pathway that enhances bladder reflex contractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…Although it could be argued that normalization of BVE could have resulted from an action of 5‐HT on the bladder itself because the instillations were performed through the bladder dome, this is unlikely. In fact, in a recent study it was shown that 5‐HT solution instilled only in the bladder of female rats or mice had no detectable effect on bladder contractility; improvements in bladder contractions were only observed when 5‐HT was applied to the urethra, where it stimulated 5‐HT 2 and 5‐HT 3 receptors …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it could be argued that normalization of BVE could have resulted from an action of 5‐HT on the bladder itself because the instillations were performed through the bladder dome, this is unlikely. In fact, in a recent study it was shown that 5‐HT solution instilled only in the bladder of female rats or mice had no detectable effect on bladder contractility; improvements in bladder contractions were only observed when 5‐HT was applied to the urethra, where it stimulated 5‐HT 2 and 5‐HT 3 receptors …”
Section: Discussionmentioning
confidence: 99%
“…Briefly, rats were anesthetized with urethane (1.2 g/kg body weight) and body temperature was kept constant using a temperature controller (WPI ATC 1000 DC, World Precision Instruments Inc, FL, USA). The bladder was exposed through a midline incision in the lower abdomen, and saline was infused through the bladder dome at a rate of 6 mL/h, using a WPI SP100IZ syringe pump (World Precision Instruments Inc, FL, USA) . The frequency and amplitude of bladder contractions was recorded after a 30‐minute stabilization period (WPI labtrax 4/16 with WPI Transbridge TBM 4 M) (World Precision Instruments Inc, FL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations